Diversidad de herpetofauna en bosque de colina baja en el área de manejo de fauna silvestre “Perufish aquarium” quebrada Yanayacu – Río Itaya, Loreto-Perú - Padilla Rimachi, Roxana Gabriela (2023)
From november 2021 to january 2022, the richness and abundance of the herpetofauna associated with the low hill forest in the Yanayacu stream – Itaya river, by lineal transect and casual encounter. It is report an richness of 39 species of amphibia and 11 reptiles with density high for Rhinella margaritifera in 300 – 800 indi/km2 and Kentropix pelviceps between 250 – 450 ind/km2; while the flora report a specific richness of 172 species predominantly of the Fabaceae with 41 species and it is concluded that the in low hill forest of “Perúfish Aquarium” that specific richness was medium for amphibia and reptiles.